Evaluation of osteogenic cell differentiation in response to bone morphogenetic protein or demineralized bone matrix in a critical sized defect model using GFP reporter mice. Issue 9 (2nd June 2014) - Alaee, Farhang; Hong, Seung‐Hyun; Dukas, Alex G.; Pensak, Michael J.; Rowe, David W.; Lieberman, Jay R.
ABSTRACT We evaluated the osteoprogenitor response to rhBMP‐2 and DBM in a transgenic mouse critical sized defect. The mice expressed Col3.6GFPtopaz (a pre‐osteoblastic marker), Col2.3GFPemerald (an osteoblastic marker) and α‐smooth muscle actin (α‐SMA‐Cherry, a pericyte/myofibroblast marker). We assessed defect healing at various time points using radiographs, frozen, and conventional histologic analyses. GFP signal in regions of interest corresponding to the areas of new bone formation was quantified using a novel computer assisted algorithm. All defects treated with rhBMP‐2 healed. In contrast, the majority of the defects in the DBM (27/30) and control (28/30) groups did not heal. Quantitation of pre‐osteoblasts demonstrated a maximal response (% GFP+ cells/TV) in the Col3.6GFPtopaz mice at day 7 (7.2% ± 6.0, p < 0.05 compared to days 14, 21, 28, and 56). The maximal response of the Col2.3GFP cells was seen at days 14 (8.04% ± 5.0) and 21 (8.31% ± 4.32), p < 0.05. In contrast, DBM and control groups showed a limited osteogenic response at all time points. In conclusion, we demonstrated that the BMP and DBM induce vastly different osteogenic responses which should influence their clinical application as bone graft substitutes. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1120–1128, 2014.